High-frequency longitudinal oscillations of the quasi-two-dimensional electron liquid - Gokhfeld, V.M.; Kirichenko, O.V.; Peschansky, V.G. (Condensed Matter Physics, 2012)
The specific character of longitudinal collective electromagnetic oscillations in a layered conductor with the quasi-two-dimensional electron energy spectrum has been analyzed. Проаналiзовано специфiку поздовжнiх колективних електромагнiтних коливань у шаруватому провiдни-ку з квазi-двовимiрним електронним енергетичним спектром.